Optimalisasi Potensi Daya Tarik Wisata Religi Masjid Raya Sultan Mahmud Riayat Syah Kota Batam - Dailami, Dailami; Thandzir, Moh.; Pristiwasa, I Wayan Thariqy Kawakibi; Sukmamedian, Haufi; Lubis, Taufik Bachrul Ulum; Rhomadani, Muhammad (CV. ITTC INDONESIA, 2025)
The Sultan Mahmud Riayat Syah Grand Mosque is one of the religious tourism icons in Batam City, known for its historical value, grand architectural design, and strong socio-religious functions. However, its potential as a religious tourism destination has not been fully optimized. This study aims to identify the mosque’s potential, analyze the inhibiting factors in its development, and formulate optimization strategies within the context of religious tourism. A qualitative-descriptive approach was used, with data collected through field observations, interviews with mosque administrators and visitors, and literature studies. The results show that the mosque has strengths in architecture, strategic location, and regular religious activities. However, lack of promotion, limited tourism-supporting facilities, and the absence of integration into city tourism packages are the main obstacles. Optimization strategies include improving supporting infrastructure, digital promotion, collaboration with travel agencies, and community involvement. With these strategies, the Sultan Mahmud Riayat Syah Grand Mosque has the potential to become a leading religious tourism center in the Riau Islands region and beyond.